Tārīkh-i Būshihr - Kāzirūnī, Muḥammad Ḥusayn Saʿādat, (Miras Maktoob, ISBN: 9789004365452., 2019)
Born in Najaf, Muḥammad Ḥusayn Saʿādat (1865-1935) first studied in his hometown and later in Shiraz. In 1898 he went to Tehran, where he started teaching at Teachers College and also at a modern primary school. During that time there was a desire to put education on a new footing, taking inspiration from western ideas. This is how Saʿādat, whose talents in education had not gone unnoticed, was appointed to found a new school in Būshihr, Iran's main port and trading hub in the Gulf area. This school, which later came to be known as the Madrasa-yi Saʿādat, soon became a famous in the region and many of its alumni had brilliant careers. Saʿādat's history of Būshihr is the product of a methodical mind that can view things in local, regional, national and international perspective. The only history of the city that we have, it is a work of incontestable importance.